2021
DOI: 10.3390/dj9070076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anatomical Parameters on the Dimensions of the Subantral Space and Sinus Mucosa Thickening after Sinus Floor Elevation. A Retrospective Cone Beam Computed Tomography Study

Abstract: Background: Various anatomical parameters might influence the surgical approach for maxillary sinus floor elevation. The objective of the present study was to retrospectively evaluate the influence of anatomical parameters on the dimensions of the subantral space and of the sinus mucosa thickening after sinus floor elevation. Material and Methods: Seventy-eight maxillary sinuses in sixty-five patients were evaluated on cone beam computed tomographies taken before surgery and after one week (t1w) and nine month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…The restorations supported by implants in those regions have shown a high success rate [1,2]. However, gaining a high predictability of that treatment is essential for an accurate assessment of a cone beam computed tomography (CBCT), aiming to identify the relevant anatomical parameters [3][4][5][6] and the presence of septa or sinus pathologies [7,8]. The thickness of the sinus mucosa is influenced by several conditions, such as the presence of apical lesions, inaccurate endodontic treatments, severe caries, and periodontal bone loss [9].…”
Section: Introductionmentioning
confidence: 99%
“…The restorations supported by implants in those regions have shown a high success rate [1,2]. However, gaining a high predictability of that treatment is essential for an accurate assessment of a cone beam computed tomography (CBCT), aiming to identify the relevant anatomical parameters [3][4][5][6] and the presence of septa or sinus pathologies [7,8]. The thickness of the sinus mucosa is influenced by several conditions, such as the presence of apical lesions, inaccurate endodontic treatments, severe caries, and periodontal bone loss [9].…”
Section: Introductionmentioning
confidence: 99%
“…This outcome of the complete absence of perforations is not in agreement with the reported outcomes of similar studies. In these studies, it was shown that sharpened edges of the granules [32][33][34][35] and implant apexes and threads [33,36] in contact with sinus mucosae produced thinning and possibly perforations over time. These differences are due to the different analytical methods applied.…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical article included in the present collection was a retrospective study on the anatomical parameters that might influence the thickening of the sinus mucosa and the dimension of the subantral space after sinus floor elevation [ 52 ]. For the evaluation, the axis ( x -axis) drawn at the base of the nose was used as reference, as suggested in various studies published by the same research group [ 4 , 19 , 20 , 29 , 30 , 31 ].…”
Section: A Synopsis Of the Special-editions Papersmentioning
confidence: 99%